2001
DOI: 10.1128/aac.45.2.553-562.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of NO Synthase Expression and Tumor Necrosis Factor Alpha Production in Macrophages by Amphotericin B Lipid Carriers

Abstract: The present study compared the abilities of different lipid carriers of amphotericin B (AMB) to activate murine peritoneal macrophages, as assessed by their capacities to produce nitric oxide (NO) and tumor necrosis factor alpha (TNF-␣). Although AMB alone did not induce NO production, synergy was observed with gamma interferon but not with lipopolysaccharide. This synergy could not be explained by the mobilization of the nuclear activation factor NF-B by AMB. On the other hand, AMB induced TNF-␣ production wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…In previous work, we compared the association of different AMB formulations with mouse peritoneal macrophages (21). This was much greater for the commercial complexes Amphotec and Abelcet than for the liposomes (AmBisome, Ampholiposomes), with the association of LC-AMB intermediate between those of these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we compared the association of different AMB formulations with mouse peritoneal macrophages (21). This was much greater for the commercial complexes Amphotec and Abelcet than for the liposomes (AmBisome, Ampholiposomes), with the association of LC-AMB intermediate between those of these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been previously reported that the association of AmB with poly(1-caprolactone) nanospheres decreased the acute toxicity of the polyene in mice (Espuelas et al, 1997). Also, we evaluated the possibility of an indirect antileishmanial activity of nanoparticles themselves (Gaspar et al, 1992;Vernier-Julienne et al, 1995) or even AmB-mediated (Mozaffarian et al, 1997;Larabi et al, 2001) through macrophage activation for cytokines and oxygen derivatives production.…”
Section: Introductionmentioning
confidence: 97%
“…Liposomal formulations of AmB reduce the toxicities observed with free AmB. However, it is also possible that different lipid-associated formulations of AmB may modify the immunomodulatory activity of the drug (31,32), thus masking the beneficial immunomodulatory properties of AmB. Despite its high cost, liposomal AmB (AmBisome) remains the best antileishmanial formulation for the treatment of VL (33).…”
mentioning
confidence: 99%